Du måste veta vad du vill - Emma Axinder (Utbildning & Demokrati)
You must know what you want. Children and the issue of consent in a Swedish educational television series. In this article, constructions of consent are analysed within a Swedish educational television series aimed at primary school pupils. Utilizing critical discourse analysis, two discourses within the program series are identified and examined: a juridical and a neoliberal discourse. Additionally, the study analyses how discourses are expressed and reinforced through e.g. different modalities. Among the study’s most significant findings is that consent is presented as something relatively simple. In relation to consent, responsibility is portrayed as a complex practice where the child is constructed in multiple ways. Thus, the child is portrayed as both a competent and responsible subject, and a subject in need of the adult’s assistance and protection.